Design of an Inclined Conveyor Drive Motor with A Capacity of 500 Kg/Minute at CV Dwitura - Saleh, Mochamad (Civiliza Publishing, Indonesia., 2025)
In an era of increasingly fierce industrial competition, speed and efficiency in the production process are important factors. Conveyors are one solution for moving goods continuously and efficiently. The purpose of this study discusses the design of an inclined conveyor drive motor with a capacity of 500 kg/minute at CV Dwitura. This research method uses a descriptive qualitative approach. Calculations include analysis of force, torque, and carrying capacity, as well as the selection of a 2.2 kW electric motor and an appropriate gearbox. The results of the study indicate that the design is able to meet the specified capacity requirements. The design of an inclined conveyor drive motor with a capacity of 500 kg/minute has been successfully realized by selecting a 2.2 kW motor and a 40-ratio gearbox. The calculation results show that the actual capacity exceeds the target, so the system is declared effective and feasible to use..